2019
DOI: 10.3390/cells8010032
|View full text |Cite
|
Sign up to set email alerts
|

A Disintegrin and Metalloprotease 15 is Expressed on Rheumatoid Arthritis Synovial Tissue Endothelial Cells and may Mediate Angiogenesis

Abstract: A disintegrin and metalloprotease 15 (ADAM15) is involved in several malignancies. In this study, we investigated the role of ADAM15 in rheumatoid arthritis (RA) angiogenesis. Soluble ADAM15 (s-ADAM15) in serum from RA and normal (NL) subjects was measured using ELISA. To determine membrane-anchored ADAM15 (ADAM15) expression in RA synovial tissues, immunohistochemistry was performed. To examine the role of ADAM15 in angiogenesis, we performed in vitro Matrigel assays and monocyte adhesion assays using human u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…ADAM15 is involved in the response to hypoxia, proteolytic ectodomain processing of cytokines, cell adhesion signaling, and angiogenesis in endothelial cells(Horiuchi et al 2003; Nishimi et al 2019). In addition, the silencing of ADAM15 can inhibit the expression of proinflammatory cytokines in rheumatoid angiogenesis(Nishimi et al 2019). Moreover, systemic proinflammatory cytokines are associated with the development of AMS and high-altitude pulmonary edema(B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADAM15 is involved in the response to hypoxia, proteolytic ectodomain processing of cytokines, cell adhesion signaling, and angiogenesis in endothelial cells(Horiuchi et al 2003; Nishimi et al 2019). In addition, the silencing of ADAM15 can inhibit the expression of proinflammatory cytokines in rheumatoid angiogenesis(Nishimi et al 2019). Moreover, systemic proinflammatory cytokines are associated with the development of AMS and high-altitude pulmonary edema(B.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of ADAM15 may play a protective role in individuals without AMS ADAM15 was identified as a candidate protective biomarker of individuals without AMS and was selected by the machine learning-based model with high accuracy to distinguish nAMS1k and nAMS4k. ADAM15 is involved in the response to hypoxia, proteolytic ectodomain processing of cytokines, cell adhesion signaling, and angiogenesis in endothelial cells (Horiuchi et al 2003;Nishimi et al 2019). In addition, the silencing of ADAM15 can inhibit the expression of proinflammatory cytokines in rheumatoid angiogenesis (Nishimi et al 2019).…”
Section: The Downregulation Of S100a12 May Not Prevent Amsmentioning
confidence: 99%
“…Proteins within ADAM and ADAMTS families may also contribute to the regulation of angiogenesis and adipogenesis [ 8 ]. For example, endothelial cell tube formation is decreased in ADAM15 small interfering RNA-treated endothelial cells, and an overexpression of ADAM17 in endothelial cells downregulates TSP-1 expression [ 101 , 102 ], suggesting that both ADAM15 and ADAM17 can stimulate angiogenesis.…”
Section: Angiogenesis and Adipose Tissue Growthmentioning
confidence: 99%
“…It has been shown that ADAM15 induces progression in several cancers including gastric [19], lung [20], colon [21]and prostate [22,23]. ADAM15 as a mediator of angiogenesis is expressed in endothelial cells and up-regulated on the angiogenic endothelial cell surface [24,25]. In addition, ADAM15 promotes cell proliferation, migration and sprouting of endothelial cells and smooth muscle cells [26].…”
Section: Introductionmentioning
confidence: 99%